(untitled) (Research, Society and Development, 2022)
This article presents the protocol of a Systematic Review that aims to analyze the scientific evidence on social network dynamics to support mothers, fathers or guardians of transgender children and adolescents. The Systematic Review will follow the following steps: identification of the research question; identification of relevant publications; selection of publications; data extraction; analysis and synthesis of evidence. The research question was formulated by adapting the PICo acronym: P (Population) AND I: (Phenomenon of interest) AND Co: (Context): “What is the scientific evidence on the social network dynamics to support mothers, fathers or guardians of transgender children and adolescents?”. Descriptors will be used for the survey of primary studies in the following databases: EMBASE, Scopus, MEDLINE, Cumulative Index to Nursing and Allied Health Literature (CINAHL), PsycInfo, Latin American and Caribbean Literature in Health Sciences (LILACS) and Web of Science. After the searches, the data will be exported to the Rayyan QCRI application, through which it will be possible to exclude duplicates and carry out the selection of materials by reading the title and abstracts by independent pairs, followed by a tiebreaker by a third reviewer if necessary. Publications that present qualitative studies with the population of mothers, fathers or guardians of transgender children and adolescents which deal with the relationships between primary and secondary social networks, or both in the context of supporting gender identity, will be included.